2018
DOI: 10.1177/0144598718778163
|View full text |Cite
|
Sign up to set email alerts
|

Thermal regime of the lithosphere and geothermal potential in Xiong'an New Area

Abstract: Investigation into the thermal regime of lithosphere is an essential part of geothermal research. The thermal state of lithosphere can be expressed as the vertical distribution of temperature. It has been found that the thermal regime of lithosphere can control the heat flow distribution and the geothermal mechanism of local geothermal fields. In this work, equilibrium temperature logs were obtained from 27 wells, and thermal conductivity and heat generation data were collected from 148 rock samples from diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Jiang et al [39] and Jiang et al [43] calculated average heat flows for mainland China of 60.9 and 60.2 mW/m 2 , respectively, indicating that the Bohai Bay basin's heat flow was higher than that of mainland China but lower than the average global heat flow of 65 ± 1.6 mW/m 2 estimated by Pollack et al [44]. We collected heat flow of 233 wells in and around the study area [42,43,[45][46][47][48][49][50], and found that it was distributed zonally in the longitudinal direction (Figure 1b Huang [32] pointed out that the heat flow in sedimentary layers is mainly related to the sedimentary environment and was unaffected by deep tectonic and lithospheric thermal structures. In order to prove the conclusion further, we chose seven wells in the two typical east-west sections.…”
Section: Contribution Of Sediments To Surface Heat Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al [39] and Jiang et al [43] calculated average heat flows for mainland China of 60.9 and 60.2 mW/m 2 , respectively, indicating that the Bohai Bay basin's heat flow was higher than that of mainland China but lower than the average global heat flow of 65 ± 1.6 mW/m 2 estimated by Pollack et al [44]. We collected heat flow of 233 wells in and around the study area [42,43,[45][46][47][48][49][50], and found that it was distributed zonally in the longitudinal direction (Figure 1b Huang [32] pointed out that the heat flow in sedimentary layers is mainly related to the sedimentary environment and was unaffected by deep tectonic and lithospheric thermal structures. In order to prove the conclusion further, we chose seven wells in the two typical east-west sections.…”
Section: Contribution Of Sediments To Surface Heat Flowmentioning
confidence: 99%
“…From the parameters provided in Table 5, crustal heat flows in the western sag, central salient, and eastern sag tectonic areas were 27, 26.2, and 25.5 mW/m 2 , respectively, and the respective conductive terrestrial heat flows were 59, 60.2, and 58.5 mW/m 2 , respectively ( Figure 6). The observed heat flow distribution in the study area [43,45,47,71] revealed a slight higher heat flow in the Bohai Bay basin comparing to the mainland China, with an average value of 68.9 mW/m 2 [43,45], but a normal heat flow in the Jizhong depression, with an average value of 63.1 mW/m 2 , which may represent the regional thermal background [47]. Specific to the Jizhong depression, low heat flow is obviously distributed in the sub-depressions, the heat flow in the main area of Baxian, Raoyang, Baoding, and Xushui sags are lower than 60 mW/m 2 (i.e., 48.9-61.6 mW/m 2 in the Baxian sag) [45,47,71] (Figure 1b).…”
Section: Crust Heat Flow Contribution and Terrestrial Heat Flowmentioning
confidence: 99%
“…Firstly, these intermountain basins mainly comprise a series of sedimentary strata from the Archaean, through the Proterozoic to Cambrian (Cope et al, 2007;Liu et al, 2013). Among the strata, the sedimentary rocks of Gaoyuzhuang Formation of the Changcheng System, Wumishan Formation of the Jixian System, and the Changping Formation of the Cambrian have been identified as good geothermal reservoirs, where the geothermal resources are accumulated via rock thermal conduction (Wang et al, 2019). Secondly, affected by the tectonic uplift and subsidence in the Yanshan area, the strata between the Late Middle Cambrian and the Late Permian, as well as the Neogene and Paleogene are missing across the basins, replaced by a wide presence of well-developed and thick-layered Cretaceous sedimentary rocks and Jurassic volcanic rocks underlain by Yanshanian granites of various thicknesses.…”
Section: Geological Settingmentioning
confidence: 99%
“…Controlled by the tectonic thermal events in Meso-Cenozoic, a higher thermal state of the lithosphere was generated in Bohai Bay Basin which the average heat flow value was 69 mW•m -2 around [13,14]. However, while in research of geotherm, abnormally high heat flow value was detected in Xiong'an New Area; especially in the Niutuozhen tectonic unit, the average heat flow can even reach 90 mW•m -2 [15,16]. When we use this heat flow value for the regional thermal structure analysis, such as the crustal temperature, an incredibly high temperature field will yield, making it very hard to understand.…”
Section: Introductionmentioning
confidence: 98%